2015
DOI: 10.1111/aor.12498
|View full text |Cite
|
Sign up to set email alerts
|

Image Processing Strategies Based on a Visual Saliency Model for Object Recognition Under Simulated Prosthetic Vision

Abstract: Retinal prostheses have the potential to restore partial vision. Object recognition in scenes of daily life is one of the essential tasks for implant wearers. Still limited by the low-resolution visual percepts provided by retinal prostheses, it is important to investigate and apply image processing methods to convey more useful visual information to the wearers. We proposed two image processing strategies based on Itti's visual saliency map, region of interest (ROI) extraction, and image segmentation. Itti's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 24 publications
0
27
0
Order By: Relevance
“…Under narrow activation spread conditions, stimulation of the retina takes A number of strategies have been proposed to achieve a desired target pattern of retinal activation. The conventional stimulation strategy sets electrode amplitudes to correspond to the desired target activations at their locations on the retina [12][13][14][15][16][17][18][19]. Under this strategy, the electrode activation pattern is simply a down-sampled (pixelated) version of the desired retinal activation pattern, with the amplitude typically scaled between the threshold and maximum allowed levels.…”
Section: Introductionmentioning
confidence: 99%
“…Under narrow activation spread conditions, stimulation of the retina takes A number of strategies have been proposed to achieve a desired target pattern of retinal activation. The conventional stimulation strategy sets electrode amplitudes to correspond to the desired target activations at their locations on the retina [12][13][14][15][16][17][18][19]. Under this strategy, the electrode activation pattern is simply a down-sampled (pixelated) version of the desired retinal activation pattern, with the amplitude typically scaled between the threshold and maximum allowed levels.…”
Section: Introductionmentioning
confidence: 99%
“…The saliency detection models are based on the visual attention mechanism and are used to extract the salient features to generate the saliency map. Common models such as the Itti and the GBVS are widely used in the field of visual prosthesis [ 12 , 13 ]. However, the saliency map detected by the common model is discrete region [ 15 , 16 ].…”
Section: Image Processing Strategies Based On Salient Object Detecmentioning
confidence: 99%
“…Their results demonstrated that the saliency map can provide clues for searching and performing tasks for users with visual prosthesis. Wang et al [ 12 ] and Li et al [ 13 ] proposed two image processing strategies based on improved Itti and GBVS model to optimize the presentation in simulated prosthetic vision, respectively. Their results demonstrated that the use of the saliency segmentation method and image processing strategies can automatically extract and enhance foreground objects and significantly improve object recognition performance towards recipients with a high-density implant.…”
Section: Introductionmentioning
confidence: 99%
“…Han et al [11] utilized feature extraction and image enhancement strategy to improve the accuracy and efficiency of object recognition. Aimed at highlighting the main object of a normal image, two different ways of pixelization [12] proved to be beneficial in daily object recognition tasks.…”
Section: Introductionmentioning
confidence: 99%
“…This study focuses on realizing the goal of obstacle avoidance for the blind based on existing visual protheses. Unlike previous studies [9], [10], [11], [12] which tried to optimize the content of phosphenes in order to improve the performances of visual tasks for the blind, our NeuCube-based obstacle avoidance system directly tells the blind the classification result of obstacle analysis, without any interaction between the prothesis wearers and the systems. As an extension of existing visual prothesis, the proposed obstacle avoidance method can make use of the down-sampled signal from information processing unit of visual prothesis, providing useful guiding information to the blind.…”
Section: Introductionmentioning
confidence: 99%